THE EFFECT OF ENTREPRENEURSHIP EDUCATION ON ENTREPRENEURIAL INTENTIONS WITH ENTREPRENEURIAL MOTIVATION AS AN INTERVENING VARIABLE - Erwanada, Nabilla Hanum; Eryanto, Henry; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the effect of entrepreneurship education on entrepreneurial intentions with entrepreneurial motivation as an intervening variable in students of the Faculty of Economics, Jakarta State University class 2017. The research method used by the researchers was a survey method with a descriptive approach, the population used was students of the Faculty of Economics. Jakarta State University class of 2017 with a sample of 139 students. The model in this study uses a path analysis model. The analytical technique used in this study uses the SEM (Structural Equation Modeling) model which is operated with the SmartPLS version 3.0 program for hypothesis testing.